Cannabis Use Disorder and Post-Deployment Suicide Attempts in Iraq/Afghanistan-Era Veterans - Adkisson, Kelsie (Arch Suicide Res, 2018)
OBJECTIVE: The objective of the present study was to use retrospective data to test the hypothesis that cannabis dependence would be associated with an increased rate of post-deployment suicide attempts. METHODS: Participants included 319 veterans who had deployed to either Iraq or Afghanistan. Study procedures involved completion of a structured clinical interview and a battery of self-report questionnaires. RESULTS: As expected, lifetime cannabis dependence was significantly associated with post-deployment suicide attempts, AOR = 7.963, p = .014, even after controlling for the effects of pre-deployment suicide attempts, posttraumatic stress disorder, depression, pain, non-cannabis substance use disorder, and gender. CONCLUSIONS: While preliminary, our findings provide the first evidence to date that heavy cannabis use may be a unique risk factor for post-deployment suicide attempts among veterans.